Through his eyes: thoughts of Hajeedar on national architectural identity of Malaysia - Asif, Nayeem; Azmin, Aida Kesuma; Abdullah, Fadzidah; Yusof, Zeenat Begam; Sanusi, Aliyah Nur Zafirah (International Organization Center of Academic Research, 2022)
This paper aims to report factual findings on the National Architecture Identity of Malaysia from the perspective of Ar. Hajeedar Abdul Majid. For almost 42 years, Ar. Hajeedar and his associates have been actively upbringing Malaysia's now booming architecture industry. The research is conducted through a descriptive analysis of an extensive interview session with the architect. Among the significant findings, it is evident that an innovative approach in architecture and ensuring harmony are highly significant in the discourse of national architectural identity. Being innovative means improving on what is already in existence. Therefore, being innovative is essential to gaining a competitive edge in every area of life. Another key finding is that harmony can only be achieved with genuine understanding, a deep awareness, and mutual respect for our differences. Harmony is, therefore, the positive and colorful celebration of our cultural diversities and the development of civilization and the human race, irrespective of our origins.